Meet the iPad and iPad mini - Carlson, Jeff; Dormans, Joris (Peachpit Press, 2014)
This practical, approachable guide by Apple guru Jeff Carlson will quickly help you get the most out of your new iPad Air and iPad mini! This hands-on guide steers you through how to navigate the home screen; launch, run, and switch between apps; use the magical Smart Cover to put to sleep and wake your iPad; change and lock screen orientation, adjust screen brightness; and conserve battery life. You'll learn how to master Multi-Touch gestures, work with text, shoot video and photos using the two built-in cameras, make FaceTime calls, sync files and content with iCloud, connect to the Internet using a Wi-Fi or 3G network, link up with Bluetooth devices, mirror video, search using Spotlight, get assistance from Siri, and more. Table of Contents: Introduction Power On and Set Up the iPad iPad Essentials Multi-Touch Gestures Work with Text Ask Siri for Assistance Sync with a Computer Connect to the Internet Using Wi-Fi Connect to the Internet Using Cellular Data Use iCloud Use Notification Center Use Control Center Connect to Bluetooth Devices Use the Cameras.